Managing a firm in the face of change - I. D. Matskulyak; V. D. Kuligin; D. I. Matskulyak (Управление)
The purpose of the publication is to study the management of the company in the context of economic changes associated with the introduction of innovations in its activities, their combinations, and taking into account the initiated entrepreneurs proper vision. In accordance with the goal, the following tasks are formulated: to achieve the company management potential, aimed at solving intra-company issues and at the same time transforming the entire market system; to identify duality of market regularity of its manifestation in modern economic environment and to propose a number of directions of its improvement on the basis of synergy of combined progressive trends introduced into production.The research methodology is based on the fundamental difference between the division of labor inside of the company and similar structures and the social division of labor itself; a well-known postulate on the commonality and features of the homotypic economic phenomena, which are the market economy and its main link – a company, organization, enterprise, etc. in the article.The results include a generalization of scientists’ views on the management of the company in conditions of change in labor, production and the economy, which occurs due to the introduction of innovations, their various combinations, into the entrepreneurial process. The company’s connection is disclosed not only with the market (exchange sphere), but also with the market economy as a cohesive whole. It is justified that both structures become the engine of economic growth. The company management itself is represented not only inside of it, but also outside, as the continuation and generation of a functioning market, market system. This is the key aspect of economic development.In conclusion, it is concluded that the management of an entrepreneurial company under conditions of change becomes the basic tool for the progress of business entities, turns into a specific rational channel for introducing combined modernization of the economy, and the search for ways to resolve the contradiction between them as part and whole, becomes the driving force of social progress.